Socio-ecological factors associated with tuberculosis infection: a systematic review - Dzulfitree Ahmad; Shamsul Azhar Shah (Universiti Kebangsaan Malaysia, 2025)
Tuberculosis (TB) is a major public health issue and poses a threat to the community with high incidence and mortality, especially in the endemic countries. Social and ecological factors have been known to cause TB transmission. Hence, it is vital to synthesise evidence to adapt to the challenges caused by these factors. As such, this review aims to explore the relationship between TB prevalence and potential social and environmental factors. We searched the electronic databases PubMed, Web of Science (WoS) and Scopus between 1st January 2013 and 31st 2024, for studies that met the following requirements: 1) original article investigating the social and environmental determinants associated with transmission of TB and; 2) the study was published in English. The Mixed Method Appraisal Tool (MMAT) assessed the study quality. We identified 484 potentially eligible published articles, of which 27 met our inclusion criteria. Findings from this systematic review showed that environmental and socioeconomic factors, mainly housing and living conditions, poverty, air quality and pollution, climate and weather, and water and sanitation infrastructure, influence the dynamics of TB transmission. These findings can guide policymakers in improving and strengthening the TB control program.